Promotion Strategy Through Go Food and Grab Food Applications at Mie Gacoan Restaurant in Dalung - Dewi, Ni Putu Mita Cintya; Massenga, Lidjah Magdalena; Juniari, Ni Kadek Eni (PT FORMOSA CENDEKIA GLOBAL, 2024)
The application or software really helps the community in working on and processing a document or task in various fields, such as making a business application for food and beverage delivery services, where there are various promotional offers that can make people interested in the application. In carrying out promotions, a strategy is needed to be able to make the products or services offered become known and attract public interest. A promotional strategy is an effective way to attract public interest and can also sell a product offered by the company by using promotional tools such as advertising, personal selling, sales promotion, and direct marketing.The purpose of this study was to determine the promotion strategy through the Go Food and Grab Food applications carried out at the Mie Gacoan restaurant in Dalung. The research method used is a descriptive qualitative method, comparing the existing research problems with related theories. Interviews with the Marketing Coordinator of the Mie Gacoan Area in Bali and Medan, as well as documentation and observation, were used to collect data. The benefits obtained from this research are that researchers can add insight into sales promotion promotion strategies and compare the theory obtained during lectures with the reality in the field.The results obtained in this study are promotional strategies through the Go Food and Grab Food applications at Mie Gacoan restaurants in Dalung when compared with the theory used in this study, namely the theory from Kotler, that there are still several promotional tools that are not implemented by the Mie Gacoan restaurants in Dalung.